Southernmost records of Entomophtoromycotina: updated review of Entomophthoralean fungal insect pathogens of Argentina - López Lastra, Claudia Cristina (2019)
The objective of this work is to further update the records of Argentinean Entomophthoralean fungal species and their geographical distribution. Our survey includes five new records of Zoophthora radicans infecting insect hosts belonging to the orders Diptera, Hemiptera, and Lepidoptera from Pampasic and Littoral regions of Argentina. These new records not only increase the host range of Entomophthoralean fungi but also their geographical distribution around the world.